A numerical investigation on the dynamic response of stiffened plated structures under moving loads. (December 2020) - Sahoo, Prakash Ranjan; Barik, Manoranjan
Abstract: The objective of this paper is to analyze the dynamic response of the stiffened plated structures under moving loads with different velocities using the finite element method. The free vibration results as well as the deflection results due to a single moving load are compared with previous studies. A finite element MATLAB code is developed to offer an efficient solution for dynamic analysis of stiffened plated structures under single and multiple moving loads in which various types of stiffener are attached to the plate. Some of the example results have been verified with FEAST (Finite Element Analysis of STructures) software to show the efficacy of the method. The parametric study is carried out by attaching various types of stiffeners in the main load carrying direction to find out the maximum deflections under single and multiple moving loads and also for the moving loads passing in opposite directions on the bridge with different velocities. The central deflection due to moving loads on stiffened plates with fixed/floating transverse frames is also analyzed in this paper.